Multidimensional poverty measurement and analysis : chapter 5 - the Alkire-Foster counting methodology - Alkire, S; Foster, J; Seth, S; Santos, M; Roche, J; Fernandez, P (2015)
This chapter provides a systematic overview of the Alkire-Foster multidimensional measurement methodology with an emphasis on the Adjusted Headcount Ratio denoted (M0). The chapter is divided into seven sections. The first shows how this measure combines the practical appeal of the counting tradition with the rigor of the axiomatic one. The second sets out the identification of who is poor using the dual-cutoff approach, and the third outlines the aggregation method used to construct the Adjusted Headcount Ratio. In the fourth, we take stock and present the main distinctive characteristics of the Adjusted Headcount Ratio, whereas the fifth section presents its useful, consistent partial indices or components. To illustrate, we present a case study using the global Multidimensional Poverty Index (MPI) in the sixth section. The final section presents the members of the AF class of measures that can be constructed in less common situations where data are cardinal.